Manufacturing method of non-zero dispersion shift optical fiber preform and prepared preform and optical fiber
By using a quartz liner and a doped quartz glass sleeve instead of PCVD deposited inner cladding, combined with a two-step melt-contraction and OVD external spray deposition method, the problems of low deposition accuracy and efficiency of non-zero dispersion-shifted optical fiber preforms are solved, and efficient manufacturing of optimized optical fiber preforms is achieved.
Patent Information
- Application Number
- CN202511169893.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-20
- Publication Date
- 2025-09-19
- Estimated Expiration
- 2045-08-20
AI Technical Summary
The deposition processing of existing non-zero dispersion-shifted optical fiber preforms requires high precision and has low efficiency. The inner cladding structure has room for improvement, especially when processing large diameters.
A quartz liner and a doped quartz glass sleeve are used instead of PCVD to deposit the inner cladding. The core rod is made by a two-step matching and melting method. The outer cladding is deposited by spraying combined with the OVD process to form a multi-layer optical fiber preform.
The accuracy and efficiency of the deposition process are improved, the parameter matching of the core layer and the inner cladding is simplified, and the resulting optical fiber preform has optimized dispersion, mode field distribution and bending loss performance, achieving higher production efficiency and product quality.
Smart Images

Figure CN120664770A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a non-zero dispersion-shifted optical fiber preform rod, and the prepared preform rod and optical fiber, belonging to the technical field of optical communication and transmission. Background Art
[0002] In the field of optical fiber communications, non-zero dispersion-shifted single-mode fiber (NZ-DSF) is a key technology developed to address the limitations of traditional optical fiber in wavelength division multiplexing (WDM) systems. Traditional single-mode fiber (corresponding to ITU-T standard G.652 fiber) has zero dispersion in the 1310nm window, but exhibits high dispersion (approximately 17 ps / (nm·km)) in the 1550nm window, limiting transmission rates over long distances. While the 1550nm window has lower loss (approximately 0.2 dB / km), dispersion causes signal pulse broadening, necessitating the frequent use of dispersion compensation modules. Dispersion-shifted DSF fiber (corresponding to ITU-T standard G.653 fiber) shifts the zero dispersion point from 1310nm to 1550nm through waveguide design, reducing dispersion in the 1550nm window. However, this characteristic causes severe four-wave mixing (FWM) nonlinear effects in WDM systems, leading to crosstalk between channels and restricting the application of dense wavelength division multiplexing (DWDM). Non-zero dispersion-shifted fiber (G.655) is a fiber specifically developed for DWDM transmission technology. It overcomes the high dispersion of G.652 fiber (non-dispersion-shifted fiber) and the severe FWM of G.653 fiber (dispersion-shifted fiber) at the low-loss 1550nm wavelength, making it the preferred fiber type for operators' fiber-optic communication systems.
[0003] A non-zero dispersion-shifted optical fiber preform consists of three parts: a core layer, an inner cladding, and an outer cladding. The core layer includes 2-4 core layers with different refractive index distributions, the inner cladding also includes 2-4 cladding layers with different refractive index distributions, and the outer cladding is a pure silica glass layer. Due to the complex refractive index profile structure of the core and inner cladding, especially the small diameter of the core layer, the narrow control range of the diameter and refractive index, and the high precision requirements, most of them use plasma chemical vapor deposition to deposit the core layer and inner cladding layer layer by layer to obtain a core rod with an integrated core layer and inner cladding. The outer cladding glass provided by OVD external vapor deposition technology is then used to form a complete optical fiber preform. The production process of the above-mentioned non-zero dispersion-shifted optical fiber core rod not only requires precise control of the deposition process of each layer, but also has low deposition efficiency. In particular, the problem of low work efficiency is more prominent when processing and depositing inner cladding with a large diameter range. In addition, there are aspects of the inner cladding structure of existing non-zero dispersion-shifted optical fibers that can be further improved. Summary of the Invention
[0004] The technical problem to be solved by the present invention is to address the deficiencies in the above-mentioned prior art and to propose a method for manufacturing a non-zero dispersion-shifted optical fiber preform and the prepared preform and optical fiber, which can not only ensure deposition processing accuracy but also have high work efficiency.
[0005] The manufacturing method and technical solution adopted by the present invention to solve the above-mentioned problems are as follows: First, an initial core rod is prepared. A multilayer core layer of a non-zero dispersion-shifted optical fiber preform core rod is deposited in a quartz liner tube through a PCVD process. After deposition, the core rod is melted and shrunk into an initial core rod in a melting and shrinking device. The multilayer core layer has three layers, and the relative refractive index difference of the multilayer core layer decreases layer by layer. The relative refractive index difference is 0.2-0.7%, and the core diameter ranges from 7 to 18 mm. The inner cladding sleeve is made of a doped quartz glass tube with a wall thickness of 6-10 mm. The relative refractive index difference is gradually distributed, with the inner surface being higher and the outer surface being lower, and presenting an upward convex shape. The relative refractive index difference of the inner surface of the sleeve (inner edge of the inner cladding) is 0.1-0.2%, and the relative refractive index difference of the outer surface (outer edge of the inner cladding) is -0.2-0%. To make a core rod, insert the initial core rod into the inner cladding casing, and melt and shrink it under low pressure in the melting and shrinking equipment to form a core rod containing the core layer and the inner cladding as one. To make an optical fiber preform, a core rod is spray-deposited with a pure silica outer cladding through an OVD process, or a core rod is covered with a pure silica outer sleeve, and then sintered or melted to make a non-zero dispersion-shifted optical fiber preform.
[0006] According to the above solution, the wall thickness of the quartz liner is 2-5 mm, and the relative refractive index difference is -0.1-0%.
[0007] According to the above scheme, the matching relationship between the initial core rod core diameter and the inner cladding sleeve wall thickness is: the initial core rod core diameter of 11-20mm is matched with the inner cladding sleeve with a wall thickness of 6-8mm, and the initial core rod core diameter of 20-28mm is matched with the inner cladding sleeve with a wall thickness of 8-10mm.
[0008] According to the above scheme, the absolute pressure of the low-pressure melting and shrinking of the core rod is controlled in the range of 0-50 mbar, and the temperature is controlled in the range of 1600°C-2200°C.
[0009] According to the above solution, the quartz liner is formed by spray deposition using the OVD process and then sintered.
[0010] According to the above solution, the inner cladding sleeve is formed by spray deposition using the OVD process and then sintered.
[0011] According to the above solution, the outer cladding wall thickness of the optical fiber preform is 35-65 mm.
[0012] According to the above scheme, the core rod of the optical fiber preform has three core layers, the relative refractive index difference Δn1 of the first core layer is 0.6-0.7%, the diameter is 3-6 mm, the relative refractive index difference Δn2 of the second core layer is 0.4-0.6%, the diameter is 5-12 mm, and the relative refractive index difference Δn3 of the third core layer is 0.3-04%, the diameter is 7-18 mm.
[0013] According to the above solution, the inner cladding of the optical fiber preform core rod is composed of two layers, the first inner cladding is composed of a quartz liner tube, and the second inner cladding is composed of an inner cladding sleeve.
[0014] The non-zero dispersion-shifted optical fiber preform of the present invention is manufactured according to the above scheme, that is, it is formed by integrating the initial core rod, the inner cladding sleeve and the outer cladding or the pure silica outer sleeve.
[0015] The non-zero dispersion-shifted optical fiber of the present invention is formed by drawing the optical fiber preform rod produced by the above-mentioned solution through a drawing tower.
[0016] According to the above solution, the non-zero dispersion-shifted optical fiber has an attenuation of ≤0.5dB / km in the 1383nm band, an attenuation of ≤0.195dB / km in the 1550nm band, and an attenuation of ≤0.200dB / km in the 1625nm band.
[0017] According to the above scheme, the dispersion slope of the non-zero dispersion-shifted optical fiber is ≤0.075ps / (nm²·km), the zero dispersion wavelength is ≤1520nm, the dispersion in the range of 1530nm~1565nm is 2~6ps / (nm·km), and the dispersion in the range of 1565nm~1625nm is 4.5~11.2ps / (nm·km).
[0018] According to the above scheme, the mode field diameter of the non-zero dispersion-shifted optical fiber at a wavelength of 1550nm is 9.2μm-10μm, the cabled cutoff wavelength is ≤1450nm, and the bending performance of the optical fiber is ≤0.03dB in a test of 100 turns around a diameter of 60mm.
[0019] The present invention has the following beneficial effects: 1. By introducing a liner and sleeve to replace PCVD deposition of the core rod inner cladding, the present invention reduces PCVD deposition time for a single core rod by approximately nine times, eliminating the dependence of non-zero dispersion-shifted optical fiber preforms on a single piece of equipment and effectively improving work efficiency. 2. The present invention utilizes a two-step matching and then melting / collapsing method for the core and inner cladding, avoiding core rod scrapping caused by mismatched parameters between the core and inner cladding during a single deposition, and providing wider manufacturing tolerances. 3. The sleeve in the present invention utilizes an upward convex graded refractive index profile. Because the inner cladding of a non-zero dispersion-shifted optical fiber regulates the fiber's dispersion characteristics, mode field distribution, and bending loss, the resulting second inner cladding, Clad2, simplifies the multi-layer stepped structure and achieves a better balance between dispersion, nonlinear effects, and bending loss. 4. The resulting non-zero dispersion-shifted optical fiber preform has an innermost core layer with the highest refractive index for strong beam confinement, and two to three outer core layers with gradually decreasing refractive index for fine-tuning waveguide dispersion and effective mode field diameter. The liner, Clad1, forms the first inner cladding, with a constant refractive index and a stepped core layer, forming the primary waveguide. The sleeve, Clad2, forms the second inner cladding. Following Clad1, a region of elevated refractive index is formed, attracting the mode field and increasing the effective area. The index then gradually decreases below Clad1, providing a continuous optical barrier and a smoother transition of the mode field to the outside. This not only increases the effective area but also shields against bend leakage. Furthermore, the convex gradient smoothes the dn / dr ratio in the elevated refractive index region, reducing the wavelength dependence of the waveguide dispersion and resulting in a lower dispersion slope. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a schematic diagram of the radial structure of the non-zero dispersion-shifted optical fiber preform of the present invention.
[0021] Figure 2 Schematic diagram of the refractive index profile of the non-zero dispersion-shifted optical fiber of the present invention. DETAILED DESCRIPTION
[0022] The present invention is further described in detail below with reference to the accompanying drawings and embodiments.
[0023] One embodiment of the present invention is Figure 1 、 2As shown, a pure silica quartz liner tube with a relative refractive index difference of 0 and a wall thickness of 4 mm is selected to deposit three core layers 1 using the PCVD process. The refractive index of the core layer decreases layer by layer. After the deposition is completed, the initial core rod is obtained by melting and shrinking at 2100°C in a melting and shrinking device. The initial core rod has a rod diameter of 20.4 mm. The relative refractive index difference of the three core layers ranges from 0.3 to 0.7%. Then, an inner cladding tube with a wall thickness of 8.5 mm is matched. The inner cladding tube is a doped quartz glass tube with a relative refractive index difference that is gradually distributed, with the inner layer being high and the outer layer being low, and presenting an upward convex shape. The relative refractive index difference of the inner surface (inner edge of the inner cladding) of the sleeve is 0.2%, and the relative refractive index difference of the outer surface (outer edge of the inner cladding) is -0.1%. The inner cladding sleeve is inserted into the initial core rod and then subjected to low-pressure shrinkage in a shrinkage device. The absolute pressure of the low-pressure shrinkage is controlled at 15 mbar and the temperature is controlled at 1800°C. After shrinkage, a core rod comprising a core layer and inner cladding is produced. The inner cladding of the optical fiber preform core rod comprises two layers: the first inner cladding 2 is formed by a quartz liner tube, and the second inner cladding 3 is formed by an inner cladding sleeve. A pure silica outer cladding 4 with a wall thickness of 45 mm is then deposited on the core rod using an OVD process. This is then sintered to form a pure silica outer cladding 4 with a wall thickness of 45 mm, thus producing a non-zero dispersion-shifted optical fiber preform. Alternatively, the core rod can be outer-coated with a pure silica outer sleeve and subjected to a shrinkage process to form a pure silica outer cladding with a wall thickness of 45 mm, thus producing a complete optical fiber preform.
[0024] The preform produced in this embodiment was drawn into a fiber using a drawing tower at a drawing speed of 1500 m / min. The resulting non-zero dispersion-shifted optical fiber had the following parameters: the first core layer had a relative refractive index difference Δn1 of 0.7% and a diameter of 4.5 μm; the second core layer had a relative refractive index difference Δn2 of 0.4% and a diameter of 8.2 μm; the third core layer had a relative refractive index difference Δn3 of 0.3% and a diameter of 11.9 μm; the first inner cladding had a relative refractive index difference Δn4 of 0 and a diameter of 20.4 μm; the second inner cladding had an inner surface relative refractive index difference Δn5 of 0.2% and an outer surface relative refractive index difference Δn6 of -0.1% and a diameter of 40.3 μm; and the outer cladding was pure silica glass with a relative refractive index difference Δn7 of 0. The optical fiber has an attenuation of 0.349 dB / km in the 1383 nm band, 0.193 dB / km in the 1550 nm band, and 0.199 dB / km in the 1625 nm band. The dispersion slope is 0.0717 ps / (nm²·km), the zero dispersion wavelength is 1484 nm, the dispersion in the range of 1530 nm to 1565 nm is 3.23 to 5.74 ps / (nm·km), and the dispersion in the range of 1565 nm to 1625 nm is 5.74 to 10 ps / (nm·km). The mode field diameter at a wavelength of 1550 nm is 9.37 μm, the cabled cutoff wavelength is 1288 nm, and the bending performance of the optical fiber is tested. In a test of 100 turns around a 60 mm diameter, the bending loss is 0.011 dB.
Claims
1. A method for manufacturing a non-zero dispersion-shifted optical fiber preform, characterized in that First, make the initial core rod, and use the quartz liner to deposit the non-zero dispersion shifted optical fiber preform core rod in the tube through the PCVD process. After the multi-layer core layer is deposited, it is melted and shrunk into an initial core rod in a melting and shrinking device. The multi-layer core layer has three layers, and the relative refractive index difference of the multi-layer core layer decreases layer by layer. The relative refractive index difference is 0.2~0.7%, and the core diameter ranges from 7~18mm. The inner cladding sleeve is made of a doped quartz glass tube with a wall thickness of 6-10 mm. The relative refractive index difference is gradually distributed, with the inner surface higher than the outer surface, and is convex. The relative refractive index difference of the inner surface of the sleeve is 0.1-0.2%, and the relative refractive index difference of the outer surface is -0.2-0%. Make the core rod, insert the initial core rod into the inner cladding casing, and melt and shrink it under low pressure in the melting and shrinking equipment to form a core rod containing the core layer and the inner cladding as one. To make an optical fiber preform, a core rod is sprayed with a pure silica outer cladding through an OVD process, or a pure silica outer sleeve is placed around the core rod, and then sintered or melted to make a non-zero dispersion shifted optical fiber preform.
2. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1, characterized in that The wall thickness of the quartz liner is 2-5 mm, and the relative refractive index difference is -0.1-0%.
3. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The matching relationship between the core diameter of the initial core rod and the wall thickness of the inner cladding sleeve is: the initial core rod with a core diameter of 11-20 mm is matched with an inner cladding sleeve with a wall thickness of 6-8 mm, and the initial core rod with a core diameter of 20-28 mm is matched with an inner cladding sleeve with a wall thickness of 8-10 mm.
4. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The absolute pressure of the low-pressure melt shrinkage is controlled within the range of 0-50 mbar, and the temperature is controlled within the range of 1600°C-2200°C.
5. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The quartz liner is formed by spray deposition using an OVD process and is sintered.
6. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The inner cladding sleeve is formed by spray deposition using an OVD process and is sintered.
7. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The outer cladding wall thickness of the optical fiber preform is 35-65 mm.
8. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The optical fiber preform core rod has three core layers, the relative refractive index difference Δn1 of the first core layer is 0.6-0.7%, the diameter is 3-6 mm, the relative refractive index difference Δn2 of the second core layer is 0.4-0.6%, the diameter is 5-12 mm, and the relative refractive index difference Δn3 of the third core layer is 0.3-04%, the diameter is 7-18 mm.
9. The method for manufacturing a non-zero dispersion-shifted optical fiber preform according to claim 1 or 2, characterized in that The inner cladding of the optical fiber preform core rod is composed of two layers, the first inner cladding is composed of a quartz liner tube, and the second inner cladding is composed of an inner cladding sleeve.
10. A non-zero dispersion-shifted optical fiber preform, characterized in that The non-zero dispersion-shifted optical fiber preform is manufactured according to the method for manufacturing a non-zero dispersion-shifted optical fiber preform according to any one of claims 1-9.
11. A non-zero dispersion-shifted optical fiber, characterized in that The non-zero dispersion-shifted optical fiber is made by drawing the non-zero dispersion-shifted optical fiber preform according to claim 10.
12. The non-zero dispersion-shifted optical fiber according to claim 11, characterized in that The optical fiber has an attenuation of ≤0.5dB / km in the 1383nm band, an attenuation of ≤0.195dB / km in the 1550nm band, and an attenuation of ≤0.200dB / km in the 1625nm band.
13. The non-zero dispersion-shifted optical fiber according to claim 11, characterized in that The non-zero dispersion-shifted optical fiber has a dispersion slope of ≤0.075 ps / (nm²·km), a zero dispersion wavelength of ≤1520 nm, a dispersion of 2 to 6 ps / (nm·km) in the range of 1530 nm to 1565 nm, and a dispersion of 4.5 to 11.2 ps / (nm·km) in the range of 1565 nm to 1625 nm.
14. The non-zero dispersion-shifted optical fiber according to claim 11, characterized in that The non-zero dispersion-shifted optical fiber has a mode field diameter of 9.2 μm-10 μm at a wavelength of 1550 nm, a cabled cutoff wavelength of ≤1450 nm, and a bending loss of ≤0.03 dB in a test of 100 turns of the optical fiber with a diameter of 60 mm.
Citation Information
Patent Citations
Large-size optical fiber preform and manufacturing method of optical fiber thereof
CN101891380A
Preform for optical fiber and its manufacturing method
JP2005247634A
Multimode optical fiber
US20060263019A1
Optical fiber preform and manufacturing method thereof
WO2010148662A1